THE IMPOSSIBILITY OF REVIVING DINAR AND DIRHAM CURRENCY SYSTEM IN THE MODERN ECONOMY WORLD - Muhammad Muflih (Journal of Indonesian Economy and Business (JIEB), 2012)
This study proves that in the discourse of fiqh, Islamic history, and Islamic banking the position of the concept of reviving the currency of dirham and dinar is very weak.Indicators that justify the conclusion of this study are: (1) there is a correspondence with historical evidence of inflation in the Islamic world, (2) there is correspondence with thoughts of fiqh, (3) there is a correspondence with modern syariah financial concept, and (4) there is a correspondence with Islamic banking attitude.This study is written to challenge the idea of Ahmad Hasan, Hifzu Rab, Khan-Mirakhor, Meera-Larbani, and ‘Umar Vadillo who state that inflation problem in Islamic world is best solved by reapplying the currencies of dinar and dirham as bases of transaction mediation. The inaccuracy of conclusion of the modern Islamic economist figures was shown by many historical facts showing the turmoil in values of these two gold bills in time of inflation. Other reasons for the fragility of these two currencies are;(i) lack of support of the fiqh expert in strengthening these currency systems as way out of the inflation-affected transaction, (ii)lack of support of fiqh experts to urge Islamic worlds to use only dinar and dirham as official currency,(iii) lack of support of Islamic banking experts to revive the use of dinar and dirham as transaction bases and remedy for inflation-affected transaction. The facts showed that the chosen system taken by fiqh and Islamic banking experts in settling the inflation-affected transaction was the strengthening of mu‘âmalah transaction system instead of alternating the currency system. The outcome of the strengthening the mu‘âmalah transaction system is a concept of price adjustment.The concept of price adjustment gives a strong implication to modern Islamic banking as an instrument of the mu‘âmalah transaction system support when facing inflation cases.Keywords: inflation, islamic banking, dinar, dirham